Specific management of post-chikungunya rheumatic disorders: a retrospective study of 159 cases in Reunion Island from 2006-2012. - Emilie Javelle; Anne Ribera; Isabelle Degasne; Bernard-Alex Gaüzère; Catherine Marimoutou; Fabrice Simon (Public Library of Science (PLoS), 2015)
BACKGROUND:Since 2003, the tropical arthritogenic chikungunya (CHIK) virus has become an increasingly medical and economic burden in affected areas as it can often result in long-term disabilities. The clinical spectrum of post-CHIK (pCHIK) rheumatic disorders is wide. Evidence-based recommendations are needed to help physicians manage the treatment of afflicted patients. PATIENTS AND METHODS:We conducted a 6-year case series retrospective study in Reunion Island of patients referred to a rheumatologist due to continuous rheumatic or musculoskeletal pains that persisted following CHIK infection. These various disorders were documented in terms of their clinical and therapeutic courses. Post-CHIK de novo chronic inflammatory rheumatisms (CIRs) were identified according to validated criteria. RESULTS:We reviewed 159 patient medical files. Ninety-four patients (59%) who were free of any articular disorder prior to CHIK met the CIR criteria: rheumatoid arthritis (n=40), spondyloarthritis (n=33), undifferentiated polyarthritis (n=21). Bone lesions detectable by radiography occurred in half of the patients (median time: 3.5 years pCHIK). A positive therapeutic response was achieved in 54 out of the 72 patients (75%) who were treated with methotrexate (MTX). Twelve out of the 92 patients (13%) received immunomodulatory biologic agents due to failure of contra-indication of MTX treatment. Other patients mainly presented with mechanical shoulder or knee disorders, bilateral distal polyarthralgia that was frequently associated with oedema at the extremities and tunnel syndromes. These pCHIK musculoskeletal disorders (MSDs) were managed with pain-killers, local and/or general anti-inflammatory drugs, and physiotherapy. CONCLUSION:Rheumatologists in Reunion Island managed CHIK rheumatic disorders in a pragmatic manner following the outbreak in 2006. This retrospective study describes the common mechanical and inflammatory pCHIK disorders. We provide a diagnostic and therapeutic algorithm to help physicians deal with chronic patients, and to limit both functional and economic impacts. The therapeutic indication of MTX in pCHIK CIR could be approved in future efficacy trials.